Retrospective analysis and modern spatiotemporal characteristics of tularemia in the territory of the West Kazakhstan and North Kazakhstan regions - U. A. Izbanova; L. Yu. Lukhnova; T. V. Meka-Mechenko; N. S. Maykanov; V. P. Sadovskaya; V. G. Meka-Mechenko; A. A. Yusupov; A. B. Makulova (Acta Biomedica Scientifica, 2023)
Rationale. An important task is to monitor the incidence of tularemia among the population of Kazakhstan. Natural foci of this infection occupy large areas. In some regions with large numbers of rodents and ectoparasites and low vaccination coverage, human cases of tularemia have been reported.The aim of the study. To carry out retrospective analysis and to study modern spatiotemporal characteristics of tularemia in the West Kazakhstan and North Kazakhstan regions in order to improve the effectiveness of preventive measures.Materials and methods. In our work, we used public records, the results of an epizootological survey of tularemia natural foci and the official data from the Departments of Sanitary and Epidemiological Control of two regions on the human cases of tularemia in 2000–2021. We used descriptive statistics methods, relative and absolute indicators of the tularemia incidence in the population for the analysis. The phenotypic and genetic properties of the strains isolated in 2000–2021 were studied according to the guidelines.Results. A retrospective analysis of the tularemia incidence among the population of the North Kazakhstan and West Kazakhstan regions showed an improvement in the epidemic situation. Over the past 20 years, 4 human cases of tularemia have been registered in the West Kazakhstan region, while the epizootic potential was quite high; more than 300 strains of the tularemia microbe were isolated during the studied period. In the North Kazakhstan region from 2000 to 2021, 11 human cases of tularemia were registered; when studying rodents, mammals and environmental objects, single positive samples for specific tularemia antibodies and antigens were detected; no strains of tularemia microbe were isolated.Conclusion. An analysis of long-term data on the epizootic and epidemic activity of tularemia natural foci, processed using descriptive statistics and GIS technology, made it possible to identify places of long-term persistence of the tularemia agent in the natural focus of the North Kazakhstan and West Kazakhstan regions and to create an electronic map of the territories endemic for tularemia to determine the scope of preventive measures.